2007
DOI: 10.1375/twin.10.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Covariance of Isometric and Dynamic Arm Contractions: Multivariate Genetic Analysis

Abstract: The purpose of the present study was to examine genetic and environmental contributions to individual differences in maximal isometric, concentric and eccentric muscle strength and muscle cross-sectional area (MCSA) of the elbow flexors. A generality versus specificity hypothesis was explored to test whether the 4 strength variables share a genetic component or common factors in the environment or whether the genetic/environmental factors are specific for each strength variable. The 4 variables under study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…Several multivariate genetic studies examined genetic and environmental contributions to individual differences in various muscle strength characteristics (11,36,37,39,41,42). These studies suggest a shared pleiotropic gene action for the different phenotypic characteristics (the same genes causing Correlations are calculated on the total GfMS sample (n ϭ 748).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several multivariate genetic studies examined genetic and environmental contributions to individual differences in various muscle strength characteristics (11,36,37,39,41,42). These studies suggest a shared pleiotropic gene action for the different phenotypic characteristics (the same genes causing Correlations are calculated on the total GfMS sample (n ϭ 748).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a shortened velocity of knee extensor muscles was found to be significantly correlated with the percentage of fast-twitch fibers in the vastus lateralis muscles (40). Second, previous studies have also suggested the presence of unique genetic causes of variance (genes causing nonshared variability in one specific muscle characteristic) (11,36,37,39,41,42). For example, the ACTN3 (11q13.1) gene, which is expressed in Z-lines of fast but not of slow muscle fibers, is believed to be one of the contributing genes in the heritability of fiber type distribution (45) and might be (in)directly involved in the presence of different curvatures of the torque-velocity relationships.…”
Section: Genome-wide Linkage Scan For Torque-velocity Relationmentioning
confidence: 91%
“…On the other hand, the findings of several multivariate genetic studies suggest a shared pleiotropic gene action for the different muscle phenotypic characteristics (Thomis et al , 1998Tiainen et al 2004Tiainen et al , 2005De Mars et al 2007). This would imply that different muscle phenotypes share the same chromosomal region with suggestive or significant evidence for linkage (De Mars et al 2008).…”
Section: Heritability Studiesmentioning
confidence: 99%
“…In studies of Finnish elderly female twins, Tiainen et al [2005] found that there was only one latent genetic component affecting both leg extensor and voluntary isometric knee extensor power testing different muscle groups in lower limbs and a r 2008 Wiley-Liss, Inc. common genetic component accounting for both hand grip and knee extension strength but not for ankle plantar extension strength [Tiainen et al, 2004]. Further, two Belgian studies reported strong genetic co-variation between maximal isometric, concentric and eccentric strength measures of the elbow flexors [De Mars et al, 2007] and isometric muscle force at different elbow angles [Thomis et al, 1997]. These results are important from a gene discovery point of view, as high genetic co-variation between different strength tests would suggest that multivariate models using simultaneously several tests could be used to increase statistical power and decrease random variation.…”
Section: Introductionmentioning
confidence: 99%